Как решить пример (7 9/17+4 4/13)-(6 9/17+3 9/13)=

Как решить пример (7 9/17+4 4/13)-(6 9/17+3 9/13)=
Гость
Ответ(ы) на вопрос:
Гость
[latex](7 \frac{9}{17}+4 \frac{4}{13} )-(6 \frac{9}{17}+3 \frac{9}{13} )=[/latex] [latex]7 \frac{9}{17}+4 \frac{4}{13}-6 \frac{9}{17}-3 \frac{9}{13}=[/latex] [latex]7 \frac{9}{17}-6 \frac{9}{17}+4 \frac{4}{13}-3 \frac{9}{13}=[/latex] [latex]1+4 \frac{4}{13}-3 \frac{9}{13}=[/latex] [latex]1+3 \frac{17}{13}-3 \frac{9}{13}=[/latex] [latex]1+3 \frac{8}{13}=[/latex][latex]4 \frac{8}{13}[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы